Effects of Renovation on Ventilation and Energy Saving in Residential Building - Cyriacus Okpalike; Francis O. Okeke; Emmanuel C. Ezema; Peter I. Oforji; Ajuluchukwu E. Igwe (Civil Engineering Journal, 2021)
Renovation usually increases the aesthetic and market value of buildings. Consequently, with the rapid growth of the city's population and skyrocketing demand for decent housing, the current trend of building conversion and renovation of existing and dilapidated property stock within city centres has become rampant. The rise in demand has pushed beyond the boundaries that every real estate investor wants to maximize profit, and it has resulted in the prevalence of uncontrolled building development, land use conversion, and non-compliance with building requirements, etc. Renovations that involve changes in building elements (especially the window system) that can influence energy saving and ventilation efficiency have thus become very common. However, the effects of building renovations on ventilation and energy efficiency have not been fully examined, particularly in Enugu (Nigeria), a rapidly growing colonial metropolis. This research employed a qualitative research approach to investigate the effects of building renovation on ventilation and energy saving in Achara layout, Enugu City, Nigeria. Four blocks of flat residential buildings were the derived sample size using a judgmental sampling technique. Physical measurements, an observation schedule, and oral interviews with site workers centred on window size, area, property, and fenestration type were used to collect empirical data involving the window system. The result reveals a very significant difference between the as-built and renovated window design systems of all studied variables. Its conclusion hinged on the fact that a renovated structure does not encourage effective natural ventilation and hence will consume more energy in cooling and lighting. It recommends the re-introduction of appropriate window systems and construction techniques for the tropical environment to reduce heat stress build-up within building units. Doi: 10.28991/CEJ-SP2021-07-09 Full Text: PDF